Connexin 43 enhances oxaliplatin cytotoxicity in colorectal cancer cell lines - Wang, S. Q.; Zhang, S. W.; Zhang, C. Z.; Zhao, Z. Y.; Wang, Y. J. (Cellular and Molecular Biology, 2017)
Oxaliplatin, a platinum-based chemotherapeutic agent, is an important first-line drug in the treatment of colorectal cancers, but drug resistance causes treatment failure. It has been reported that gap junctional communication can enhance the cytotoxicity of platinum drugs.  The gap junction formed of connexin proteins provides a direct pathway for electrical and metabolic cell-cell interaction. The voltage-dependent gating of gap junction allows small hydrophilic molecules and ions to permeate to adjacent cells. Connexin 43 is a diagnostic marker for cancer therapy and the predominant connexin isoform in many cell types. The purpose of this study was to investigate the role of connexin 43 in oxaliplatin activity by using colorectal cancer cell lines. LoVo and HCT116 cell lines were used for analysis. Connexin 43 expression was confirmed by western blot and immunocytochemistry. MTT, western blot, "Parachute” dye-coupling assays and reactive oxygen species measurement were used to detect cytotoxicity and the inhibition of connexin 43 expression induced by oxaliplatin. Results showed that connexin 43 enhanced oxaliplatin cytotoxicity through gap junctional communication function and high concentration of oxaliplatin inhibited connexin 43 expression to counteract its cytotoxicity. This study suggested that connexin 43 could be considered a molecular target of oxaliplatin activity in colorectal cancer.